Evaluation of antipyretic activity of hydroalcoholic extract of Corchorus depressus Linn. in Escherichia coli–induced pyretic rabbits. (28th July 2018) - Ahmad, Saeed; Akram, Muhammad; Ali Shah, Syed Muhammad; Sultana, Sabira
This study was conducted to investigate the antipyretic effect of the hydroalcoholic extract of Corchorus depressus Linn. against Escherichia coli ( E. coli )-induced pyrexia in rabbits. Hydroalcohalic extracts of C. depressus were given orally at 25, 50, and 100 mg/kg for antipyretic affect in E. coli -induced fever in rabbits. The animals were divided into five groups of five each. Among these five groups, three received various doses of experimental treatments, whereas the fourth one served as positive control and received paracetamol. The fifth group of animals served as negative control and received no treatment. The body temperature of the rabbits was measured rectally over a period of 5 h. C. depressus exhibited better effects at dose rate of 25, 50, and 100 mg/kg. The hydroalcoholic extract of C. depressus has significant antipyretic effect. These results lend support to the popular use of C. depressus in traditional medicine as a remedy for pyrexia and suggest that the characterization of the principles for such activity deserves further investigation.